Focal Versus Combined Focal Plus Radial Extracorporeal Shockwave Therapy in Lateral Elbow Tendinopathy: A Retrospective Study - Caterina Delia; Gabriele Santilli; Vincenzo Colonna; Valerio Di Stasi; Eleonora Latini; Antonello Ciccarelli; Samanta Taurone; Antonio Franchitto; Flavia Santoboni; Donatella Trischitta; Sveva Maria Nusca; Mario Vetrano; et al. (Journal of Functional Morphology and Kinesiology)
Background: Lateral epicondylitis of the elbow, commonly known as tennis elbow, is a musculoskeletal disorder characterized by pain and degeneration of the common extensor tendon. Despite various treatments, optimal management remains debated. Objective: This study aimed to compare the effectiveness of focal extracorporeal shockwave therapy (F-ESWT) alone versus a combination of focal and radial pressure waves (F-ESWT+R-PW) in treating chronic lateral epicondylitis. Methods: This retrospective observational study included 45 patients diagnosed with chronic lateral epicondylitis divided into two groups based on the treatment received: group A (F-ESWT, n = 23) and group B (F-ESWT+R-PW, n = 22). Both groups underwent three weekly sessions of their respective treatments. Patients were also given a home exercise protocol. Primary outcomes were assessed using the Visual Analog Scale (VAS) for pain and the Patient-Rated Tennis Elbow Evaluation (PRTEE) for pain and functional impairment at baseline (T0), 4 weeks (T1), 12 weeks (T2), and 24 weeks (T3) post-treatment. Secondary outcomes included grip strength and ultrasonographic measurements of common extensor tendon (CET) thickness and vascularization. Results: Significant improvements in VAS and PRTEE scores were observed in both groups at all follow-up points. Group B showed greater pain reduction at T1 (VAS: 3.0 ± 1.6 vs. 4.43 ± 1.47; p < 0.005) and T2 (VAS: p < 0.030) compared to group A. Functional outcomes (PRTEE) also favored group B at T1 (p < 0.030) and in the pain section at T2 (p < 0.020). Grip strength improved similarly in both groups. CET thickness showed no significant differences at T3. Vascularization decreased significantly in both groups, with a non-significant trend favoring group B. Conclusions: The combined F-ESWT+R-PW therapy proved more effective than F-ESWT alone in the short- to mid-term management of chronic lateral epicondylitis, significantly enhancing pain reduction and functional outcomes. The combination of focal and radial pressure waves offers a superior therapeutic approach, leveraging the distinct mechanisms of each modality for better clinical results. Further research is needed to confirm these findings and establish long-term efficacy.